Molecular insights into the divergence and diversity of post-testicular maturation strategies. (1st November 2020) - Nixon, Brett; Cafe, Shenae L.; Eamens, Andrew L.; De Iuliis, Geoffry N.; Bromfield, Elizabeth G.; Martin, Jacinta H.; Skerrett-Byrne, David A.; Dun, Matthew D.
Abstract: Competition to achieve paternity has coerced the development of a multitude of male reproductive strategies. In one of the most well-studied examples, the spermatozoa of all mammalian species must undergo a series of physiological changes as they transit the male (epididymal maturation) and female (capacitation) reproductive tracts prior to realizing their potential to fertilize an ovum. However, the origin and adaptive advantage afforded by these intricate processes of post-testicular sperm maturation remain to be fully elucidated. Here, we review literature pertaining to the nature and the physiological role of epididymal maturation and subsequent capacitation in comparative vertebrate taxa including representative species from the avian, reptilian, and mammalian lineages. Such insights are discussed in terms of the framework they provide for helping to understand the evolutionary significance of post-testicular sperm maturation. Graphical abstract: Image 1 Highlights: Eutherian sperm undergo complex post-testicular maturation prior to fertilization. The need for post-testicular sperm maturation varies in sub-therian vertebrates. We discuss evolutionary forces that have shaped these divergent maturation strategies.